2020
DOI: 10.1186/s12876-020-01354-4
|View full text |Cite
|
Sign up to set email alerts
|

The diffuse-type gastric cancer epidemiology enigma

Abstract: Background: Intestinal and diffuse gastric adenocarcinomas differ in clinical, epidemiological and molecular features. However, most of the concepts related to the intestinal-type are translated to gastric adenocarcinoma in general; thus, the peculiarities of the diffuse-type are underappreciated. Results: Besides its growing importance, there are many gaps about the diffuse-type carcinogenesis and, as a result, its epidemiologic and pathogenetic features remain poorly understood. Conclusions: Alternative hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 30 publications
1
20
0
3
Order By: Relevance
“…There are few reports addressing microbiome differences among Lauren types. A need for augmentation of the number of analyzed cases, including full clinical information, may shed light on putative differences among histological, localization, and staging features [29].…”
Section: Healthy Versus Unhealthy Gastric Microbiomementioning
confidence: 99%
“…There are few reports addressing microbiome differences among Lauren types. A need for augmentation of the number of analyzed cases, including full clinical information, may shed light on putative differences among histological, localization, and staging features [29].…”
Section: Healthy Versus Unhealthy Gastric Microbiomementioning
confidence: 99%
“…At present, the differences between DGC and IGC have been insufficiently explored and understood; differences in etiology, location, incidence, genetic profiles, among others, have been observed (52). The GC CNA-EMT network (Figure 5) was generated with relevant genes according to different criteria: frequency among patients as well as genetic connections, reported pathways, and experimental associations with several databases: EMTDB, The Human Protein Atlas, COSMIC (53), Cancer Hallmark Genes (CHG) database (54).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, epidemiological studies have shown the association of H. pylori abundance with different GC subtypes. For instance, the incidence of intestinal-type GC exhibits a markedly declining trend, whereas the diffuse type shows an increasing trend in both high-and low-risk areas for GC [49]. The decreased incidence of intestinal-type GC has been principally attributed to improved food preservation and declined H. pylori infection rates [1,4].…”
Section: Gastric Microbiota In Gastric Cancermentioning
confidence: 99%